Uterine rupture at the University of Calabar Teaching Hospital, Calabar; Nigeria: a six-year review - Odusolu, Patience O.; Uduigwomen, Praise A.; Eyong, Edu M.; Okpebri, Komommo O.; Egbe, John J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Ruptured uterus is one of the major complications of labour which contributes significantly to maternal and perinatal morbidity and mortality in low-resource and developing countries. Periodic review is necessary to determine the magnitude, risk factors and feto maternal outcomes to aid to plan prevention reduce maternal and fetal mortality are needed. The objective of the study was to determine the prevalence, risk factors, management options, and feto-maternal outcomes of uterine rupture in University of Calabar Teaching Hospital (UCTH), Calabar. Methods: Records of women with uterine rupture between January 2013 and December 2018 were retrieved. Sociodemographic data, clinical presentations, surgical options, fetal and maternal outcomes were recorded and analysed. Data was presented in frequencies and percentages. Results: During the study period, total number of deliveries was 11,382 with 41 ruptured uterus giving it an incidence of 0.36 percent. Twenty-eight (71.8%) of the patients were unbooked while 11 (28.2%) were booked. The mean age was 28.08 and majority were para 2 and 3 at 10 (25.6%). Obstructed labour was the commonest cause 28 (71.8%). Rupture of scar contributed to 8 cases (20.5%). Commonest presentation was abdominal pain 25 (64.1%). The commonest surgical procedure was uterine repair alone 21 (53.8%), while repair and bilateral tubal ligation was 8 (20.5%) and hysterectomy 9 (23.1%). Maternal mortality was 1 (2.6%) while fetal mortality was 32 (82.05%). The cause of maternal death was anaemic heart failure. Conclusions: Predisposing factors for uterine rupture at UCTH, Calabar are mostly modifiable. As such integrated efforts to prevent occurrence and ensure prompt management to reduce maternal and fetal mortality are needed.